P16 positive oropharyngeal small cell cancer: A case report. (October 2021) - Al Masalmeh, Nada; Kukreja, Geetika; Zaiem, Feras; Raza, S. Naweed; Kim, Harold; Nagasaka, Misako; Sukari, Ammar
Abstract: Extra-pulmonary small cell carcinomas (EPSCC) are rare malignancies. Like small cell lung cancer (SCLC), they are aggressive malignancies with dismal prognosis. We here report a case of a middle-aged man who presented with odynophagia and cervical lymphadenopathy. Diagnostic workup confirmed the diagnosis of locally-advanced p16-positive oropharyngeal cancer (OPC) with a surprising histology of small cell cancer, suggesting a human papilloma virus (HPV)-related oropharyngeal cancer with small cell differentiation. HPV oropharynx infection is a well-known risk factor for squamous cell carcinoma of the oropharynx, but it is unknown if it may increase the risk of other OPC histology.